Relationship between isometric strength parameters and specific volleyball performance tests: Multidimensional modelling approach - Majstorovic, N. J.; Dopsaj, M. J.; Grbic, V. M.; Savic, Z. S.; Vicentijevic, A. R.; Nešic, G. P. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Volleyball player`s performance depends on a combination of technical-tactical skills and an optimum level of general and specific physical fitness. OBJECTIVE: The purpose of the study was to compare the results of three isometric strength tests with the results of four specific volleyball performance tests using a novel Multidimensional Modelling Approach. METHODS: In a cross-sectional study 80 male (age = 16.2 ± 1.7 yrs.) and 116 female (age = 16.1 ± 1.5 yrs.) volleyball players performed two testing sessions consisting of ankle extensor, handgrip, and lumbar isometric strength tests, followed by countermovement tests, modified X test and medicine ball throw. RESULTS: Principal Component Analysis, with 51.38% to 64.87% of variances explained, was used to group results from multiple tests into a single score: isometric force (F max Score), rate of force development (RFD max Score), and specific performance tests (Specific Score). Calculated F max Score, and RFD max Score values showed low (r = 0.310-0.416), but statistically significant (p < 0.01) correlations with Specific Score. Regression analysis showed 17.3% and 9.6% influence of F max and 16.9% and 10.1% influence of RFD max on specific abilities for male and female sample respectively. CONCLUSIONS: The findings derived from the isometric strength tests are not related to those obtained from specific volleyball performance tests. However, the advantages of isometric tests and their findings may be of a comparative clinical value in management of sports injury in volleyball players.